Dilema Etika pada Akuntan Sebuah Studi Persepsi Mahasiswa Akuntansi - Wijayanti, Dwi Marlina; Kasingku, Frisky Jeremi; Rukmana, Risa (Jurnal Dinamika Akuntansi dan Bisnis, 2017)
Internal factors play an important role in decision making, especially under conditions of a dilemma. Therefore, we examined the internal factors of individuals consisting of gender, age, and level of education in the deliberations and decision-making when faced with ethical dilemmas. This study used a survey by Aluchna Mikolajczyk (2013) and Eweje Brunon (2010) to collect data. 106 students who were respondents in this study were divided into 87 undergraduate students and 19 postgraduate students. Hypothesis testing used was nonparametric chi-square test to see the differences in the perception of respondents. As a result, women were more often indicate or face the ethical dilemma rather than in men. Age did not affect the attitude when it was faced with moral dilemmas for the development of the higher age of respondents, where it is not necessarily better than the moral development of the respondents with a younger age. There was no different in perception between age and level of education to ethical dilemmas. Practical contribution of this research was taken into consideration by the personnel manager when recruiting human resources and become knowledgeable in instilling ethics education from an early age, so that the moral development of the individual can arrive at the highest stage.